The magnitude of anemia and its associated factors among pregnant women in Hawela Tula Sub-city of Hawassa, Hawassa, Ethiopia - Tesfaye, Sileshi; Petros, Legese; Tulu, Israel Alemayehu; Feleke, Fentaw Wassie (Frontiers in Nutrition, 2024)
Introduction: Anemia is one of the most serious health problems impacting people worldwide. The disease is quiet, moving slowly and producing only a few physical symptoms. Anemia during pregnancy raises the risk of premature birth, low birth weight, and fetal anomalies, and it can have a substantial financial impact on society and families. However, there was a paucity of studies on the magnitude and associated factors of anemia among pregnant women in southern Ethiopia.Objective: This study aimed to assess the magnitude and associated factors of anemia among pregnant women attending antenatal care in the Hawella Tula sub-city of Hawassa City in 2021.Methods: Institution-based cross-sectional study was done on 341 randomly selected pregnant women attending antenatal care clinics. Data were obtained using a standardized semi-structured questionnaire. To identify the associated factors for the magnitude of anemia logistic regression model was used with an adjusted odds ratio (AOR) with 95% confidence intervals (CI) was calculated.The prevalence of anemia was pregnant women attending antenatal care in health facilities of Hawella Tula Sub-city was 113 (33.7%) with a 95% confidence interval (CI) (28.8, 38.9). Maleheaded household (AOR=2.217, 95% CI: 1.146, 4.286), rural resident (AOR= 3.805, 95% CI: 2.118, 6.838), early marriage below 18 years (AOR=2.137, 95% CI: 1.193, 3.830) and recurrent of illness during pregnancy (AOR=3.189, 95% CI: 1.405, 7.241) were associated factors for anemia.Anemia prevalence among pregnant women was 113 (33.7%). Anemia in pregnant women was associated with rural residents, early marriage age below 18 years, and repeated illnesses during pregnancy.